Humor as Seen In Spiderman Far From Home Film by Jon Watss - tri wahyuni sundari; diana rozelin (English Language, Linguistics, Literature, And Education Journal, 2020)
This study aims to analyze humor as seen in Spiderman Far From Home film by Jon Watss. This film showed that humor occurs by maxim flouting, it causes misunderstanding between speakers to hearers, because the participants do not obey the rules of the maxim in conversation. The researcher has employed qualitative research and descriptive method to find out the differences about classification forms of humor, how do flouting of maxim occur in humor, and functions of humor, it used the similarities data.The researcher analyzed the flouting of the maxim that occur in Spiderman Far From Home film to describe the functions of humor. The researcher used the humor theory by Martin that discusses forms of humor, maxim theory by H. Paul Grice that discusses types of flouting maxim, and the functions of humor by Attardo’s theory. The researcher uses the techniques of documentation for collecting the data. Based on the analysis that has been done, the researcher has found out that there are forms and types of humor. First joke, spontaneous in; irony, satire, sarcasm, overstatement, self-deprecation, teasing, clever replies a serious statement, double entendres, pun, and unintentional humor. Second, there are the maxim of quality flouting, the maxim of quantity flouting, maxim of relevance flouting, and maxim of manner flouting. Third, their categories and types function of humor which indicated social management; social control, ingratiation, discourse management, and repair. And another category functions of humor; decommitment, probing, salvaging, and defunctionalization.